Clinical correlation to differences in ranibizumab and aflibercept vascular endothelial growth factor suppression times. Issue 11 (17th February 2016) - Fauser, Sascha; Muether, Philipp S
Abstract : Aim: To determine clinical correlations to intraocular vascular endothelial growth factor A (VEGF-A) suppression times (VSTs) on the treatment of neovascular age-related macular degeneration (nAMD) with ranibizumab (Lucentis) or aflibercept (Eylea). Methods: Seven of 89 treatment-naïve nAMD eyes showed persistent choroidal neovascular membrane (CNV) activity throughout a spectral domain optical coherence tomography (SD-OCT)-driven pro re nata (PRN) regimen of intravitreal ranibizumab injections over 28±4 months. The treatment was switched to PRN aflibercept injections and patients were followed for another 15±2 months. A total of 160 aqueous humour specimens were collected before the intravitreal injections, and their VEGF-A concentrations were assayed by Luminex multiplex bead analysis (Luminex, Austin, Texas, USA). Intraocular VEGF-A concentrations were correlated to CNV activity shown by SD-OCT. Results: The mean duration of suppression of VEGF-A concentrations in aqueous humour below the lower limit of quantification of our assay was 34±5 (26–69) days for ranibizumab and 67±14 (49–89) days for aflibercept (p<0.001). The percentual reduction of central retinal volume (CRV) 6 weeks after injection was higher for aflibercept compared with ranibizumab (p=0.009). The time point of clinical re-activity occurred about 50% earlier than the respective VST for each ranibizumab and aflibercept. Conclusions: The VST under aflibercept treatment exceeded that under ranibizumab treatment by a factor of 2. This difference correlated with differential clinical CRV reduction 6 weeks after the respective injection. For both medications, clinical activity was found at a time point as early as 50% of the individual VST. Trial registration number: NCT01213667, post-results